Self-actualization of individuals with intellectual disability: role of the environment - Shcherbakova, Anna M. (Social Welfare: Interdisciplinary Approach, 2012)
The article focuses on the issue of self-actualization in children and adolescents with intellectual disability. It demonstrates the importance of fostering a positive personality potential to enhance self-actualization capacity. The article discusses the role of the close and broad social environment in supporting successful activities of mentally challenged children and adolescents. It stresses the need to design custom activity-based environments to ensure self-actualization of the mentally handicapped. It provides data from several empirical studies covered by the same approach.
Keywords: intellectual disability; mental handicap; self-actualization; self-efficacy; sociocultural approach; rehabilitation environment